(untitled) (Scientific journal of the Fergana State University, 2026)
The article explores the theoretical and practical aspects of developing anti-corruption competence in future teachers through an integrative approach. It analyzes effective methods and a system-functional model for competence formation. The findings propose innovative strategies to prevent corruption in the educational system.